UNDERSTANDING OF EARLY NUMBER AND NUMERATION OF MATHEMATICS AT IIUM EDUCARE, GOMBAK, MALAYSIA - Muhajir, Muhajir (Universitas Dr. Soetomo, 2019)
The understanding of number of mathematics for the young children is very crucial in their life. The purpose of this study is to find out the methods used in teaching young children’s construction of mathematics. Also to find out the understanding and different ability between the boys and girls in early number and numeration in mathematics. This study direct observation using checklist method. A sample size 12 children aged ranging from 4, 5 and 6 years-old consisting of 2 boys and 2 girls from selected class. The results indicate that there are three concepts in teaching and learning of early number and numeration of mathematics (a. Memorizing the sequence of the number names, b. Symbol of the number, and c. Development model in number). In addition, the concepts for teaching in early number needed the variation and interactive approaches in model of teaching for this subject. Finally, the results indicate that there are similarity abilities between boys and girls for 4 year-old and 6 year-old, while for 5 year-old, indicated that there are different abilities between girls and boys in pre-mathematics. Implications and recommendations are stated for stakeholders. Keywords: Early Numbers, Numeration and IIUM Educare